رأس المال النفسي وعلاقتة بالتدفق النفسي لدى طالبات كلية التربية الأساسية بدولة الكويت - الرشيدي، نشميه عمهوج حمدان (جامعة عين شمس - مركز الإرشاد النفسي, 2023)
هدفت الدراسة إلى التعرف على مستوى رأس المال النفسي والتدفق النفسي لدى طالبات كلية التربية الأساسية بدولة الكويت، وأثر متغيرات (التخصص، العمر، الحالة الاجتماعية) على ذلك، والكشف عن العلاقة بين رأس المال النفسي والتدفق النفسي، واشتملت الأدوات على مقياس رأس المال النفسي ومقياس التدفق النفسي، وتألفت العينة من (٥٤٦) طالبة. وأظهرت النتائج أن الدرجة الكلية لرأس المال النفسي وجميع الأبعاد (الكفاءة الذاتية، الأمل، المرونة، التفاؤل) فوق المتوسط لدى الطالبات، وأن الدرجة الكلية للتدفق النفسي وجميع الأبعاد (وضوح الأهداف، التركيز والاندماج في الأداء، الإحساس بالتحكم) مرتفعة لدى الطالبات. وأشارت النتائج إلى عدم وجود فروق دالة إحصائياً عند مستوى (٠,٠٥) بين متوسطات درجات أفراد عينة الدراسة حول (الكفاءة الذاتية، الأمل، المرونة) والدرجة الكلية لرأس المال النفسي وفقاً لمتغيري التخصص والحالة الاجتماعية بينما توجد فروق حول التفاؤل، وعدم وجود فروق حول (الكفاءة الذاتية، الأمل، التفاؤل) والدرجة الكلية لرأس المال النفسي وفقاً لمتغير العمر، بينما توجد فروق حول المرونة. كما أشارت النتائج إلى عدم وجود فروق حول (التركيز والاندماج في الأداء، الإحساس بالتحكم) والدرجة الكلية للتدفق النفسي وفقاً لمتغير التخصص، بينما توجد فروق حول وضوح الأهداف، وعدم وجود فروق حول (وضوح الأهداف، الإحساس بالتحكم) والدرجة الكلية للتدفق النفسي وفقاً لمتغير العمر، بينما توجد فروق حول التركيز والاندماج في الأداء، وعدم وجود فروق حول التركيز والاندماج في الأداء وفقاً لمتغير الحالة الاجتماعية، بينما توجد فروق حول باقي الأبعاد والدرجة الكلية للتدفق النفسي. كما أظهرت النتائج وجود علاقة ارتباطية متوسطة دالة إحصائياً بين الدرجة الكلية لرأس المال النفسي والتدفق النفسي. The study aimed to identify the level of psychological capital and psychological flow for students of the College of Basic Education in the State of Kuwait, and the effect of the variables (specialization, age, social status), and to reveal the relationship between psychological capital and psychological flow. The tools included psychological capital scale and psychological flow scale, and the sample consisted of (546) female students. The results showed that the total degree of psychological capital and all dimensions (self-efficacy, hope, flexibility, optimism) is above average for female students, and the total degree of psychological capital and all dimensions (clarity of goals, focus and integration in performance, sense of control) is high. The results indicated that there were no statistically significant differences between the averages of sample about (self-efficacy, hope, flexibility) and the total degree of psychological capital due to specialization and social status variables, while there are differences about optimism. And there are no differences about (self efficacy, hope, optimism) and the total degree of psychological capital due to age variable, while there are differences about flexibility. The results also indicated that there were no differences about (focus and integration in performance, sense of control) and the total degree of psychological flow due to specialization variable, while there were differences about clarity of goals, and no differences about (clarity of goals, sense of control) and the total degree of psychological flow due to age variable While there are differences in focus and integration in performance, and there are no differences about focus and integration in performance due to social status variable, while there are differences about the rest of the dimensions and the overall degree of psychological flow. The results also showed a medium correlation statistically significant between the total degree of psychological capital and psychological flow.
Keywords: علم النفس الرياضي -- التفوق الرياضي -- المهام الصعبة